THE SPIRIT OF CHARACTER EDUCATION PRESENTED IN MISS GRAYLING’S POLITENESS STRATEGIES - Kartika Widiastuti, Maria; Bram, Barli (PARADIGM: Journal of Language and Literary Studies, 2024)
Centering students’ life on character education which cultivates virtue is approachable by politeness strategies that transform threatening utterances into something empowering and more appropriate. Therefore, this study investigates politeness strategies used by Miss Grayling in The Second Form at Malory Towers written by Enid Blyton, as the principal, who instill students’ good character by highlighting their potential and making the suggestion less offensive and aims to connect linguistic concept implication with real issues in education. In answering the research question “How do Miss Grayling’s politeness strategies have roles in emphasizing character education?” and “What are the purposes of politeness strategies used by Miss Grayling?” Qualitative content analysis is employed by dissecting the specific parts to make categorization according to Brown and Levinson’s Politeness Strategies before data analysis. The results show that Miss Grayling uses giving gifts, asking for a reason, being optimistic, hedging/questioning, and impersonalizing to emphasize the value of character education by emphasizing the institution’s generation in educating students, motivating students to use her positive side, encouraging honesty and responsibility, highlighting students’ character aside from score result, and emphasizing the importance of wisdom.